2004
DOI: 10.1620/tjem.203.77
|View full text |Cite
|
Sign up to set email alerts
|

Differential Localization of Brain-Type and Epidermal-Type Fatty Acid Binding Proteins in the Adrenal Gland of Mice

Abstract: In immuno-light and -electron microscopy, brain-type fatty acid binding protein (B-FABP) is localized in the sustentacular cells enclosing the chromaffin cells in the adrenal medulla. This represents another new feature commonly shared by the sustentacular cells and ganglionic satellite cells, the latter of which has already been reported to localize this molecule, and suggests a common feature in lipid metabolism shared by the two cells enclosing peripheral neurons and paraneurons. On the other hand, epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…However, its mRNA was later found to be expressed in various tissues including adipose tissue 5,8,9,[12][13][14][15][16][17][18][19][20][21][22][23] . Krieg et al 5) examined levels of C-FABP mRNA in mouse tissues, and found that the mRNA was most abundant in stratified epithelia of the epidermis and tongue.…”
Section: Discussionmentioning
confidence: 99%
“…However, its mRNA was later found to be expressed in various tissues including adipose tissue 5,8,9,[12][13][14][15][16][17][18][19][20][21][22][23] . Krieg et al 5) examined levels of C-FABP mRNA in mouse tissues, and found that the mRNA was most abundant in stratified epithelia of the epidermis and tongue.…”
Section: Discussionmentioning
confidence: 99%
“…With this consideration, together with recent increasing attention paid to the functional significance of glial cells in the neural function (Fields & Stevens-Graham, 2002;Miller, 2005), the present study attempted to reveal the detailed entire morphology of the sustentacular cells in the adrenal gland of adult and newborn mice in comparison with those cells in the adult carotid body and sympathetic ganglion by immunohistochemistry at the light microscopic level using the antibody for brain-type-fatty acid-binding protein (B-FABP), which has already been shown to be a specific marker for the sustentacular cells as well as the other associated cells of glial nature (Yun et al 2004;Owada et al 2006). Special attention was paid to the morphological feature of the sustentacular cellular envelopes themselves.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that adrenal medullary sustentacular cells are modified Schwann cells, because these cells express immunoreactivity for S-100 [3]. In general, S-100 protein has already been shown to be a specific marker of adrenal medullary sustentacular cells as well as the other associated cells of glial nature [9,15,24].…”
Section: Introductionmentioning
confidence: 99%